55.6k views
0 votes
Given the functions f(x)=3x−2and g(x)=−4x+1. Find (f+g)(x) and simplify completely.

Given the functions f(x)=3x−2and g(x)=−4x+1. Find (f+g)(x) and simplify completely-example-1
User BueKoW
by
4.7k points

2 Answers

0 votes

Answer:

(f+g)(x) = -x - 1

Explanation:

f(x)=3x−2

g(x)=−4x+1

(f+g)(x) = 3x -2 -4x+1

= -x - 1

User Edward Van Kuik
by
5.4k points
5 votes


\\ \sf\Rrightarrow f(x)=3x-2


\\ \sf\Rrightarrow g(x)=-4x+1

Now


\\ \sf\Rrightarrow (f+g)(x)


\\ \sf\Rrightarrow f(x)+g(x)


\\ \sf\Rrightarrow 3x-2+(-4x+1)


\\ \sf\Rrightarrow 3x-2-4x+1


\\ \sf\Rrightarrow 3x-4x-2+1


\\ \sf\Rrightarrow -x-1

User Sasha Goldshtein
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.